Prospects for healthcare personnel training in the public health system of Ukraine - Khomenko, I.M.; Ivakhno , O.P.; Pershehuba , Ya.V.; Piven , N.V. (Medicni Perspektivi, 2021)
Purpose: scientific substantiation of training of medical personnel for the public health system of Ukraine. During 2017-2020, the Department of Public Health conducted a systematic analysis of public health staffing in Ukraine, developed countries and Europe. For the first time, a model of formation of specialists’ competencies for the public health system of Ukraine in the postgraduate education program with a multidisciplinary approach to training is substantiated and developed, which includes such disciplines as epidemiology, hygiene, medical statistics, laboratory diagnostics, information technology, legal law and others. This enables to reveal the tools and methods of system management, improve the availability and quality of work during the formation and development of the industry. The need for medical education for public health specialists who are ready to perform basic operational functions to preserve and strengthen the health of the population of Ukraine has been established. For the first time, methodological approaches to the improvement of higher medical education at the undergraduate and postgraduate levels have been scientifically substantiated, taking into account modern requirements for the functioning of the public health system; competence models of the public health specialist in modern conditions of realization of his activity are created; standards of higher education at the first (bachelor’s) and second (master’s) levels in the specialty 229 “Public health” in the field of knowledge 22 “Health Care” have been developed.